Method for constructing antifouling antibacterial biological membrane on surface of steel
By building anti-fouling and antibacterial biofilm based on microfluidic aquaculture on the steel surface and introducing aluminum elements, the shortcomings of existing marine anti-fouling coatings in terms of environmental protection and durability are solved, efficient and environmentally friendly anti-fouling effect is achieved, and the mechanical properties and stability of the material are improved.
Patent Information
- Application Number
- CN202510329513.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-06-20
AI Technical Summary
Existing marine antifouling coatings have challenges in taking into account antifouling efficiency and environmental protection. The harmful chemicals in traditional coatings will damage the marine ecosystem, while the durability and cost of bionic antifouling coatings still need to be solved. At the same time, the lack of mechanical properties of diatomaceous earth in engineering applications limits its widespread use.
By constructing antifouling biofilm on the surface of steel based on microfluidic farming diatoms, biofilm is formed using the adhesion and proliferation process of diatoms, and the mechanical properties and antibacterial properties of the biofilm are enhanced by the introduction of aluminum elements.
The diatom biofilm with excellent antifouling and antibacterial properties was achieved on the surface of the steel, which improved the mechanical properties and stability of the material, reduced the toxic effects of aluminum in the environment, and enhanced the long-term stability and corrosion resistance of the biofilm.
Smart Images

Figure CN120174377A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of antifouling coatings, and particularly relates to a method for constructing an antifouling biofilm on the surface of steel by culturing diatoms based on microfluidics. Background Art
[0002] As an important guarantee for national marine security, the development of warships is directly related to a country's marine rights and interests. However, the seawater temperature and humidity in China's sea areas are very suitable for the growth and reproduction of marine organisms. The presence of a large number of fouling organisms poses a serious challenge to the operation of warships. Marine organisms such as large algae, barnacles, and shells are prone to attaching to the surface of warships, forming biological fouling, increasing the hull weight and surface friction resistance, resulting in increased fuel consumption and bringing high operating costs. In addition, seawater, as a strong electrolyte, is extremely corrosive to metal materials such as steel. Warships suffer huge economic losses every year due to marine corrosion and fouling problems, greatly shortening the service life of warships and affecting their combat capabilities and long-term service life.
[0003] To address the problem of marine fouling, marine antifouling coatings have evolved over the years and become the most economical and efficient antifouling measure currently. However, although the harmful chemical substances in traditional antifouling coatings can effectively prevent the attachment of fouling organisms, they will seriously damage the marine ecosystem. For example, coatings containing organotin compounds have a broad-spectrum antifouling effect, but are toxic to non-target organisms after entering the marine environment, and even disrupt the marine food chain, leading to ecological imbalance. Therefore, how to balance antifouling efficiency and environmental friendliness has become a key issue in the current research on marine antifouling coatings. In recent years, environmentally friendly bionic antifouling coatings, as an emerging technology, have received wide attention. By mimicking the antifouling mechanisms in nature, such as shark skin and the lotus leaf effect, they physically prevent the attachment of fouling organisms and reduce environmental damage. Such coatings not only have good antifouling effects but are also friendly to the marine environment, avoiding the toxic effects of traditional coatings. However, bionic antifouling coatings still face challenges such as insufficient durability and high costs in applications. Therefore, the development of new coatings with broad-spectrum antifouling and environmental friendliness remains an important task in the field of marine antifouling, which is of great significance for the service of warships, economic benefits, and ecological protection.
[0004] Meanwhile, the special environment in the deep - sea area also provides potential solutions. Deep - sea areas represented by the Mariana Trench are considered the ultimate convergence places for sediments, accumulating a large amount of sediments composed of diatoms. Research has found that in the deep - sea area with a water depth of 5800 meters to 10954 meters, large - scale diatom mat sediments are formed by Ethmodiscus rex. These sediments are mainly composed of a mixture of aeolian dust and volcanic materials, indicating that the input of Asian aeolian dust may be the main driving factor for diatom blooms. Diatomaceous earth, a siliceous ooze rich in silicon dioxide and microbial remains, has a chemical composition mainly of SiO2·nH2O, with characteristics such as high water content, large porosity, low strength, and high compressibility, showing strong water - storage capacity and adsorption characteristics in geological structures. This characteristic provides inspiration for the development of eco - friendly antifouling coatings, indicating that its natural antifouling mechanism can be used for synthesizing biofilms to improve the eco - friendliness and stability of materials. However, although diatomaceous earth shows significant potential in ecological applications, its relatively poor mechanical properties still limit its wide use in engineering applications. The undrained shear strength of diatomaceous earth is usually less than 1.5 kPa. Under external disturbance or mechanical extrusion, the material strength rapidly decreases and it is easy to lose structural stability. Therefore, when developing antifouling coatings based on diatom characteristics, how to effectively improve its mechanical properties, especially to maintain a stable antifouling effect during long - term service, remains a key issue that needs in - depth research and solution. Summary of the Invention
[0005] In order to overcome the above - mentioned deficiencies of the prior art, the present invention provides a method for constructing an antifouling biofilm by culturing diatoms on the surface of steel based on microfluidics.
[0006] The technical solution of the present invention is as follows:
[0007] A method for constructing an antifouling and antibacterial biofilm on the surface of steel, comprising the following steps:
[0008] (1) Inoculate the pre - cultured diatom algal species into the f / 2 medium; add the aluminum - containing compound solution to the medium in a gradient addition manner and mix well; the specific component ratio of the f / 2 medium is prepared according to the culture volume as follows: To prepare 1 L of F / 2 medium, gradually add 75 mg of sodium nitrate (NaNO3), 30 mg of sodium silicate (Na2SiO3·9H2O), 5 mg of dipotassium hydrogen phosphate (K2HPO4), 25 mg of magnesium sulfate (MgSO4·7H2O), 20 mg of calcium sulfate (CaSO4·2H2O), 5 mg of potassium chloride (KCl), 3.15 mg of iron chloride (FeCl3·6H2O), 0.5 μg of vitamin B12, and 0.05 μg of biotin to sterile distilled water;
[0009] (2) Keep the pH value and temperature in the culture medium stable; Immerse the steel material in the adjusted F / 2 culture medium, and perform intermittent lighting on the culture medium to simulate the natural day-night rhythm; After a period of time, steel with an antifouling and antibacterial biofilm on its surface is obtained. The steel is stainless steel or low-carbon steel material, cut into sheets with a size of 5 cm × 5 cm. After cleaning and then under sterile conditions, the steel is completely immersed in the adjusted F / 2 culture medium, and the immersion depth is 3 - 5 cm. After a period of time, steel with an antifouling and antibacterial biofilm on its surface is obtained; Then test its properties, mainly mechanical properties and antibacterial properties; The test steps are as follows: After soaking for a period of time, such as 7 days, 11 days or 14 days, take out the steel sheet, gently rinse its surface with deionized water to remove unbound diatoms and culture medium residues, and then dry it naturally or in a low-temperature oven not exceeding 60 °C to ensure the integrity and stability of the biofilm; Use an optical microscope and a scanning electron microscope to characterize the morphology of the biofilm, use XRD to characterize the phase composition of the biofilm, and test the mechanical properties of the steel with an antifouling and antibacterial biofilm on its surface through mechanical properties; Conduct an antifouling test in a simulated marine environment, and observe the resistance of the diatom biofilm to the attachment of microorganisms, especially the inhibitory effect on the attachment of bacteria.
[0010] Preferably, the aluminum-containing compound is an aluminum salt; The gradient addition method is that after adding a certain amount of the aluminum-containing compound solution at a fixed flow rate, after an interval of time, add a certain amount again at a fixed flow rate; Multiple additions and intervals are the gradient addition method. Generally, add 3 - 10 times, and the interval time is not less than 10 minutes.
[0011] Preferably, the diatom strain is inoculated into the f / 2 culture medium at a volume ratio of 1∶(5 - 15); Further preferably, the diatom strain is inoculated into the f / 2 culture medium at a volume ratio of 1∶10.
[0012] Preferably, the aluminum-containing compound is an aluminum salt; After adding a certain amount of the aluminum-containing compound solution at a fixed flow rate, after an interval of time, add a certain amount again at a fixed flow rate; Multiple additions and intervals are the gradient addition method.
[0013] Preferably, the final concentration of aluminum ions in the culture medium is 0.01 mM - 1.00 mM.
[0014] Preferably, add a buffer solution to keep the pH value in the culture medium between 7.0 - 8.5; Control the temperature between 20 - 26 °C.
[0015] Preferably, the buffer solution is a phosphate solution.
[0016] Preferably, the light intensity used is 100 - 160 μmol·m -2 ·s -1A white cold light source is used to irradiate the culture medium at intervals to simulate the natural circadian rhythm. The light irradiation and the interval time are both 12 h.
[0017] Preferably, each step is controlled by a microfluidic system. The preparation method of the microfluidic system includes the following steps: designing a microfluidic chip including a serpentine channel and a Raman detection channel; preparing an SU-8 mold, spin-coating SU-8 3050 epoxy photoresist on a silicon wafer to form a 100-μm-thick coating, and obtaining a channel structure through ultraviolet exposure and development; mixing a polydimethylsiloxane prepolymer and a curing agent in a ratio of 10:1, degassing, pouring the mixture onto the SU-8 mold, baking at 70 °C for 5 h for curing and demolding to form a polydimethylsiloxane chip; after punching, bonding the polydimethylsiloxane chip to a glass slide through oxygen plasma to obtain a microfluidic chip with a serpentine channel and a Raman detection channel; that is the microfluidic system.
[0018] Preferably, the serpentine channel is 150 μm wide and the Raman detection channel is 800 μm wide; the heights of the serpentine channel and the Raman detection channel are 100 μm.
[0019] In the method of the present invention, the pH value is controlled by adding an appropriate amount of phosphate buffer solution and maintained between 7.0 and 8.5. The light condition uses a white cold light source, and the light intensity is adjusted to 100-160 μmol·m -2 ·s -1 , and a cycle of 12 h of light irradiation and 12 h of darkness is set to simulate the natural circadian rhythm. The temperature is controlled between 20-26 °C, and a constant culture environment is maintained through the temperature control module of the microfluidic chip. During the culture process, the growth state of diatoms is monitored in real time, and the flow rate and the solution replacement frequency are adjusted to ensure the stability of the culture conditions.
[0020] The beneficial effects of the present invention:
[0021] The method for constructing an anti-fouling and antibacterial biofilm on the surface of steel in the present invention. The formation mechanism of the biofilm mainly includes the attachment and proliferation process of diatoms. After obtaining nutrients in the culture medium, diatoms rapidly proliferate through cell division and bind to the steel surface through self-secreted adhesion substances (such as polysaccharides) to form a stable biofilm. This biofilm can not only effectively reduce the corrosion rate of the metal surface but also improve the anti-fouling property of the material to a certain extent. The method for constructing an anti-fouling and antibacterial biofilm on the surface of steel in the present invention can further enhance the mechanical properties and antibacterial properties of the biofilm by introducing aluminum elements into the culture medium. Although aluminum element is not an essential element for the growth of diatoms, its dissolved aluminum element is toxic to microorganisms under certain environmental conditions; in the method of the present invention, through the "isomorphic substitution" mechanism of aluminum, it is absorbed by diatoms and fixed in its silica shell to form stable Al-O bonds; this substitution not only improves the structural strength of the shell but also effectively reduces the concentration of dissolved aluminum in the environment, thereby reducing the toxic effect on microorganisms. In addition, the phenomenon of fixed aluminum enhances the stability of the biofilm, enabling it to maintain good antibacterial and anti-fouling effects under environmental changes, and improving the reliability and durability of the material in practical applications.
[0022] The method of the present invention constructs an anti-fouling biofilm on the surface of steel by microfluidically culturing diatoms based on a microfluidic system. The method of the present invention improves the mechanical properties of the steel and the stability and anti-fouling properties of the biofilm on the steel surface by establishing a microculture method for in-situ tracking and monitoring of diatom cells at the cellular level and a matching detection method for the physiological response of algal cells. The microfluidic system of the present invention is provided with multiple channels to precisely adjust the fluid flow rate and direction, and is equipped with a light source and a temperature control system to simulate the optimal light and temperature conditions to promote the rapid growth of diatoms. An appropriate amount of aluminum source is added to the culture medium, and the concentration and addition rate of aluminum elements are controlled through specific channels to promote the mineralization of the diatom cell wall and improve the mechanical properties of the steel with the biofilm; finally, the antibacterial and anti-algal ability of the biofilm is enhanced through the uptake and "fixation" of aluminum by diatoms, and a diatom biofilm with excellent anti-fouling properties is constructed on the surface of the steel.
[0023] The method of the present invention is based on the silica structure of diatom frustules and its formation mechanism. The frustules of diatoms are formed by silica in a highly ordered nanostructure. Usually, silicon combines with four oxygen atoms to form strong Si-O bonds (about 800 kJ / mol), endowing the diatom frustules with extremely high mechanical strength and rigidity, and enhancing their compressive resistance. Diatoms absorb silicate and carry out the frustule formation process (biomineralization) within the cells, gradually generating this complex silica shell. In the method of the present invention, by adding aluminum elements during the diatom cultivation process, isomorphous substitution of aluminum elements in the diatom frustule formation process is achieved, that is, aluminum atoms combine with four-coordinated oxygen atoms and partially replace the positions originally occupied by silicon atoms. Although the strength of the Al-O bond (about 500 kJ / mol) is lower than that of the Si-O bond, the introduction of aluminum can enhance the compactness of the shell structure, reduce the porosity, and thus make the overall structure more stable; this densification effect effectively reduces the solubility of diatom frustules in water, increases the Young's modulus of the material, and enhances the mechanical properties of the shell; at the same time, the addition of aluminum also improves the antibacterial and anti-algal properties of the diatom biofilm by changing the mass transport path of the shell or promoting mineral deposition, enhancing its long-term stability and corrosion resistance in the marine environment. In addition, introducing aluminum elements during the microfluidic cultivation of diatoms based on the microfluidic system makes it have a significant antifouling effect. Although aluminum shows toxicity to fish and microorganisms under certain environmental conditions (especially in acidic environments), the dissolved aluminum ions can interfere with the ionic permeability and nutrient uptake of cell membranes and even cause the death of organisms; however, diatoms can fix aluminum in the silica shell structure through the "isomorphous substitution-like" mechanism; after aluminum atoms replace some of the silicon positions, they no longer exist in a free state, effectively reducing the toxic effects of dissolved aluminum on the environment and microorganisms; this fixation process reduces the solubility of aluminum in water, weakens its harmfulness in the environment, enhances the performance of diatoms in antifouling applications, and thus improves the antibacterial and anti-algal properties of the diatom biofilm. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the microfluidic system of the present invention.
[0025] Figure 2 It is a physical diagram of the microfluidic system of the present invention.
[0026] Figure 3 It is a microscope photo of the biofilms of Examples 1 - 4.
[0027] Figure 4 It is a scanning electron microscope photo of the biofilms of Examples 1 - 4.
[0028] Figure 5 It is a displacement-load diagram of the metals and biofilms of Examples 1 - 4.
[0029] Figure 6XRD patterns of the biofilms obtained in Example 1 and Example 3.
[0030] Figure 7 Bacteriostatic rates of the biofilms of Examples 1-4.
[0031] Figure 8 Bacteriostatic rings of the biofilms of Examples 1-4. Detailed implementation manners
[0032] The technical solutions of the present invention will be described in detail below in conjunction with embodiments. The following embodiments are only used to illustrate the present invention and should not be construed as limiting the protection scope of the present invention. For those conditions not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments whose manufacturers are not indicated, they are all conventional products that can be obtained by purchasing in the market.
[0033] Example 1
[0034] (1) Microfluidic system design: Use AutoCAD software to design a microfluidic chip. The chip includes a 150-μm-wide serpentine channel and an 800-μm-wide Raman detection channel, with a channel height of 100 μm, suitable for the culture and observation of single-cell diatoms. Subsequently, an SU-8 mold is prepared by soft lithography technology. The SU-8 3050 epoxy photoresist is spin-coated on a silicon wafer to form a 100-μm-thick coating, and after ultraviolet exposure and development, a channel structure is obtained. Then, the PDMS prepolymer and the curing agent are mixed at a ratio of 10:1, degassed, and poured onto the SU-8 mold, cured at 70 °C for 5 hours, and demolded to form a PDMS chip. After punching, the PDMS chip is bonded to a glass slide through oxygen plasma, and finally a microfluidic chip with a serpentine channel and a Raman detection channel is obtained, providing a platform for studying the growth and metabolic status of diatoms.
[0035] (2) Diatom cultivation process: According to the standard formula of Guillard's F / 2 medium, its composition includes nitrate, phosphate, silicate and trace elements. The specific component ratios are prepared as follows according to the cultivation volume: To prepare 1 L of F / 2 medium, 75 mg of sodium nitrate (NaNO3), 30 mg of sodium silicate (Na2SiO3·9H2O), 5 mg of dipotassium hydrogen phosphate (K2HPO4), 25 mg of magnesium sulfate (MgSO4·7H2O), 20 mg of calcium sulfate (CaSO4·2H2O), 5 mg of potassium chloride (KCl), 3.15 mg of iron chloride (FeCl3·6H2O), 0.5 μg of vitamin B12 and 0.05 μg of biotin are gradually added to sterile distilled water. The pre-cultured diatom strain is inoculated into the medium at a volume ratio of 1:10 and injected through the first input channel of the microfluidic chip, with the flow rate set at 5 μL / min. Subsequently, a 0.1 mM aluminum sulfate solution is injected into the third input channel of the microfluidic chip at a flow rate of 2 μL / min each time, added once every 2 hours for a total of 5 times, so that the concentration of aluminum ions in the final medium gradually reaches 0.05 mM to ensure thorough mixing with the medium. The pH value is controlled by adding an appropriate amount of phosphate buffer solution to maintain it at 7.0. The light condition uses a white cold light source, and the light intensity is adjusted to 100 μmol·m -2 ·s -1 , and a cycle of 12 hours of light and 12 hours of darkness is set to simulate the natural circadian rhythm. The temperature is controlled at 20 °C, and a constant cultivation environment is maintained through the temperature control module of the microfluidic chip. During the cultivation process, the growth state of diatoms is monitored in real time, and the flow rate and solution replacement frequency are adjusted to ensure the stability of the cultivation conditions.
[0036] (3) Construction of a biofilm on the steel surface: A stainless steel or low-carbon steel material sheet with a size of about 5 cm × 5 cm after cleaning treatment is immersed in the above-adjusted F / 2 medium; under sterile conditions, the immersion depth is 3 - 5 cm; the immersion time is 7 days; during the immersion process, the temperature is kept constant at 20 °C, and the light condition is a 12-hour light and 12-hour darkness cycle; a biofilm will gradually form on the steel surface. After 7 days of immersion, the steel is taken out and the surface of the steel is gently rinsed with deionized water to remove unbound diatoms and residual medium, and then naturally dried or dried in a low-temperature oven (not exceeding 60 °C) to ensure the integrity and stability of the biofilm; then tests are carried out.
[0037] Figure 3 a- Figure 3 a2 is the microscope photo of the obtained biofilm, Figure 4 a- Figure 4 a1 is the scanning electron microscope photo of the obtained biofilm. From Figure 3 a- Figure 3 a2 and Figure 4 a-Figure 4 a1 It can be seen that algae and rod-shaped bacteria are attached to the biofilms in this example. The biofilms are mainly flocculent, and a large number of inorganic and organic particles adhere around the bacteria and diatoms; pH = 7, light intensity 100 μmol·m -2 ·s -1 , temperature is 20 °C, and the structure of the biofilm is relatively loose when the immersion time is 7 days. Figure 5 Sample 1 is the displacement-load diagram of the metal and biofilm in this example; from Figure 5 it can be seen that in its mechanical properties, the yield strength is 740 Mpa, the tensile strength is 803 Mpa, and the fracture strength is 489 Mpa. Figure 6 This is the XRD diagram of the biofilm obtained in this example. From Figure 6 it can be seen that the characteristic diffraction peaks of SiO2 and Fe are contained in the biofilm, and the multiple appearances of the SiO2 diffraction peaks verify the successful preparation of the diatom biofilm, which is consistent with the main component SiO2 of diatoms. Figure 7 This is the antibacterial rate of the biofilm; Figure 8 This is the antibacterial ring of the biofilm. From Figure 7 and Figure 8 it can be seen that the antibacterial rate of the biofilm in this example is 92.97%, and the diameter of the antibacterial ring of the biofilm is 12.1 mm.
[0038] Example 2
[0039] (1) The same as Example 1.
[0040] (2) During the diatom cultivation process, according to the standard formula of Guillard's F / 2 medium, the same as Example 1. The pre-cultured diatom algal species were inoculated into the medium at a volume ratio of 1:10 and injected through the first input channel of the microfluidic chip, and the flow rate was set at 5 μL / min. Subsequently, a 0.3 mM aluminum sulfate solution was injected into the third input channel of the microfluidic chip at a flow rate of 2 μL / min each time, added once every 1.5 hours, and added a total of 6 times, so that the concentration of aluminum ions in the final medium gradually increased to 0.15 mM, ensuring uniform distribution and maintaining a stable culture environment. The pH value was kept at 7.5; the light intensity was 120 μmol·m -2 ·s -1 , a cycle of 12 hours of light and 12 hours of darkness was set; the temperature was controlled at 22 °C; a constant culture environment was maintained through the temperature control module of the microfluidic chip. During the cultivation process, the growth status of diatoms was monitored in real time, and the flow rate and solution replacement frequency were adjusted to ensure the stability of the culture conditions.
[0041] (3) Constructing a biofilm on the steel surface, the same as Example 1. After 9 days of cultivation, the steel was taken out for testing.
[0042] Figure 3 b-Figure 3 b2 is the microscopic photograph of the obtained biofilm, Figure 4 b- Figure 4 b1 is the scanning electron microscope photograph of the obtained biofilm. From Figure 3 b- Figure 3 b2 and Figure 4 b- Figure 4 b1, it can be seen that algae and rod-shaped bacteria are found to adhere to the biofilm in this embodiment. The biofilm is mainly flocculent, and a large number of inorganic and organic particles adhere around the bacteria and diatoms; pH = 7.5, light intensity 120 μmol·m -2 ·s -1 , temperature is 22 °C, and when the immersion time is 9 days, the structure of the biofilm is relatively thin. Figure 5 Sample 2 is the displacement-load diagram of the metal and biofilm in this embodiment; from Figure 5 it can be known that among its mechanical properties, the yield strength is 790 Mpa, the tensile strength is 895 Mpa, and the fracture strength is 586 Mpa. From Figure 7 and Figure 8 it can be seen that the antibacterial rate of the biofilm in this embodiment is 93.16%, and the diameter of the antibacterial ring of the biofilm is 13.8 mm.
[0043] Example 3
[0044] (1) The same as Example 1.
[0045] (2) In the process of diatom culture, according to the standard formula of Guillard's F / 2 medium, the same as Example 1. The pre-cultured diatom algal species are inoculated into the medium at a volume ratio of 1:10 and injected through the first input channel of the microfluidic chip, and the flow rate is set at 5 μL / min. Subsequently, the 0.5 mM aluminum sulfate solution is injected into the third input channel of the microfluidic chip at a flow rate of 2 μL / min each time, added once every 1 hour, and added 8 times in total, so that the concentration of aluminum ions in the final medium reaches 0.25 mM, ensuring that the medium and aluminum ions are fully mixed and maintaining a stable pH environment. The pH value is controlled by adding an appropriate amount of phosphate buffer solution and kept at 8.0; the light intensity of the white cold light source is 140 μmol·m -2 ·s -1 , setting a cycle of 12 hours of light and 12 hours of darkness to simulate the natural day-night rhythm. The temperature is controlled at 24 °C.
[0046] (3) Constructing the biofilm on the steel surface, the same as Example 1. After 11 days of culture, the steel is taken out for testing.
[0047] Figure 3 c- Figure 3 c2 is the microscopic photograph of the obtained biofilm, Figure 4 c- Figure 4c1 is the scanning electron microscope photo of the obtained biofilm. From Figure 3 c- Figure 3 c2 and Figure 4 c- Figure 4 c1, it can be seen that algae and rod-shaped bacteria are attached to the biofilm in this example. The biofilm is mainly flocculent, and a large number of inorganic and organic particles adhere around the bacteria and diatoms; pH = 8, light intensity 140 μmol·m -2 ·s -1 , temperature is 24 °C, and the structure of the biofilm is relatively uniform and dense when the immersion time is 11 days. Figure 5 Sample 3 is the displacement-load diagram of the metal and biofilm in this example; from Figure 5 it can be known that in its mechanical properties, the yield strength is 882 Mpa, the tensile strength is 982 Mpa, and the fracture strength is 612 Mpa. From Figure 7 and Figure 8 it can be seen that the antibacterial rate of the biofilm in this example is 96.12%, and the diameter of the antibacterial ring of the biofilm is 14.1 mm. Figure 6 This is the XRD diagram of the biofilm obtained in this example. From Figure 6 it can be seen that the characteristic diffraction peaks of SiO2 and Fe are contained in the biofilm obtained in this example, and the multiple appearances of the SiO2 diffraction peaks verify the successful preparation of the diatom biofilm, which is consistent with the main component SiO2 of diatoms.
[0048] Example 4
[0049] (1) The same as Example 1.
[0050] (2) In the process of diatom cultivation, according to the standard formula of Guillard's F / 2 medium, the same as Example 1. The pre-cultured diatom strain is inoculated into the medium at a volume ratio of 1:10 and injected through the first input channel of the microfluidic chip, and the flow rate is set at 5 μL / min. Subsequently, the 1.2 mM aluminum sulfate solution is injected into the third input channel of the microfluidic chip at a flow rate of 2 μL / min each time, and added once every 0.5 hours for a total of 10 times, so that the concentration of aluminum ions in the final medium reaches 0.6 mM, ensuring uniform distribution of the aluminum ion concentration gradient and optimizing the diatom growth and biofilm formation conditions. The pH value is controlled by adding an appropriate amount of phosphate buffer solution and maintained at 8.5. The light condition uses a white cold light source, and the light intensity is 160 μmol·m -2 ·s -1 , and a cycle of 12 hours of light and 12 hours of darkness is set. The temperature is controlled at 26 °C.
[0051] (3) Construct the biofilm on the steel surface, the same as Example 1. After 14 days of cultivation, take out the steel for testing.
[0052] Figure 3 d- Figure 3 d2 is the microscopic photograph of the obtained biofilm, Figure 4 d- Figure 4 d1 is the scanning electron microscope photograph of the obtained biofilm. From Figure 3 d- Figure 3 d2 and Figure 4 d- Figure 4 d1, it can be seen that algae and rod-shaped bacteria are found to adhere to the biofilm in this example. The biofilm is mainly flocculent, and a large number of inorganic and organic particles adhere around the bacteria and diatoms; pH = 8.5, light intensity 160 μmol·m -2 ·s -1 , the temperature is 26 °C, and when the immersion time is 14 days, the structure of the biofilm is relatively uniform and dense. Figure 5 Sample 4 is the displacement-load diagram of the metal and biofilm in this example; from Figure 5 it can be seen that in its mechanical properties, the yield strength is 900 Mpa, the tensile strength is 995 Mpa, and the fracture strength is 630 Mpa. From Figure 7 and Figure 8 it can be seen that the antibacterial rate of the biofilm in this example is 94.38%, and the diameter of the antibacterial ring of the biofilm is 13.7 mm.
[0053] Table 1 shows the mechanical properties of the biofilms in Examples 1-4; the comparative sample is the biofilm without adding aluminum element, and the conditions are the same as those in Example 1.
[0054] Table 1 Mechanical property data
[0055]
[0056] In summary, the biofilm is composed of algae, rod-shaped bacteria and inorganic / organic particles, forming a flocculent structure. pH = 7, light intensity 100 μmol·m -2 ·s -1 , the temperature is 20 °C, and when the immersion time is 7 days (Example 1), the structure of the biofilm is relatively loose. As the pH value, light intensity, temperature and time increase, the biofilm tends to be uniform and dense; the synergistic effect of light, temperature and time promotes the development of the biofilm from loose to uniform and dense, indicating that energy input and extended culture time contribute to improving the density of the biofilm. Figure 5 It shows that with the extension of the immersion time and the strengthening of other conditions, the mechanical properties of the steel plate gradually increase; the yield strength, tensile strength and fracture strength increase with the increase of the aluminum ion concentration and reach the highest at 0.6 mM (Example 4) (tensile strength 995 MPa); appropriately increasing the aluminum ion concentration from 0.25 mM to 0.6 mM, the culture time from 10 to 14 days and the temperature of 24 °C contribute to improving the mechanical properties. Figure 7 and Figure 8It shows that Example 3 exhibits the highest antibacterial rate (96.12%) and the largest antibacterial ring diameter (14.1 mm); this indicates that the antibacterial rate and the antibacterial ring diameter reach the optimum at pH = 7.5, light intensity of 140 μmol·m -2 ·s -1 , 24 °C, and on the 11th day; the antibacterial rate decreases instead with an overly long treatment time (14 days, Example 4), which may be due to the decreased activity of metabolites caused by the overly long treatment time; the antibacterial effect under the condition of pH = 7.5 is overall better than that at pH = 7, indicating that a weakly alkaline environment is more conducive to the secretion of antibacterial active substances. Regarding the comparison of the concentration effects, in Example 1 (aluminum ion concentration in the culture medium is 0.05 mM), the biofilm is relatively loose, and both the antibacterial ability and the mechanical properties are low. In Example 3 (aluminum ion concentration in the culture medium is 0.25 mM), the biofilm is dense and uniform, and the antibacterial effect is the best. In Example 4 (aluminum ion concentration in the culture medium is 0.6 mM), the mechanical properties are the highest, but the antibacterial performance slightly decreases. This shows that an appropriate amount of aluminum ions helps to enhance the stability of the biofilm, but too high a concentration may inhibit the growth of diatoms and affect its antibacterial ability.
[0057] In summary, the selection of the optimal conditions needs to balance the antibacterial rate and the mechanical properties; if antibacterial is the primary goal, an aluminum ion concentration of 0.25 mM is better; if the mechanical properties need to be considered, it is recommended to control the aluminum ion concentration above 0.25 mM, keep the pH above 7.0 such as 8.0, and set the light intensity at 120 - 140 μmol·m -2 ·s -1 , so as to optimize the stability and antifouling ability of the biofilm.
[0058] The above is only used to introduce the specific implementation manners of the present invention in detail, but the technical solutions proposed by the present invention are not limited to the above methods. Without departing from the basic principles of the present technology, equivalent modifications and changes made by those skilled in the art to the technology proposed by the present invention should all be covered within the scope of the claims of the present invention.
Claims
1. A method for constructing an antifouling and antibacterial biofilm on a steel surface, characterized in that: The steps include: (1) inoculating the pre-cultured diatom species into an f / 2 culture medium; adding an aluminum compound solution into the culture medium in a gradient addition manner and mixing thoroughly; (2) Maintaining the pH value and temperature of the culture medium stable; immersing the steel material in the adjusted F / 2 culture medium, and irradiating the culture medium with intermittent light to simulate the natural circadian rhythm; after a period of time, a steel material having an antifouling and antibacterial biofilm on the surface is obtained.
2. The method according to claim 1, characterized in that Diatom species were inoculated into f / 2 culture medium at a volume ratio of 1:(5-15).
3. The method according to claim 1, characterized in that The aluminum-containing compound is an aluminum salt; after a certain amount of the aluminum-containing compound solution is added at a fixed flow rate, a certain amount is added again at a fixed flow rate after a certain interval; multiple additions and intervals are called a gradient addition method.
4. The method according to claim 3, characterized in that The final concentration of aluminum ions in the culture medium is 0.01 mM-1.00 mM.
5. The method according to claim 1, characterized in that The buffer solution was added to keep the pH value of the culture medium between 7.0 and 8.5; the temperature was controlled between 20 and 26°C.
6. The method according to claim 5, characterized in that The buffer solution is a phosphate solution.
7. The method according to claim 1, characterized in that The light intensity was 100-160 μmol·m -2 ·s -1 The culture medium was illuminated at intervals by a white cold light source, with the illumination and interval times being 12 h respectively.
8. The method according to claim 1, characterized in that Each step is controlled by a microfluidic system. The preparation method of the microfluidic system comprises the following steps: designing a microfluidic chip including a serpentine channel and a Raman detection channel; preparing an SU-8 mold, spin-coating SU-83050 epoxy photoresist on a silicon wafer to form a coating layer with a thickness of 100 μm, and developing the coating layer through ultraviolet exposure to obtain a channel structure; mixing a polydimethylsiloxane prepolymer and a curing agent in a ratio of 10:1, pouring the mixture on the SU-8 mold after degassing, baking at 70°C for 5 hours to cure the mixture, and demoulding the mixture to form a polydimethylsiloxane chip; after punching, combining the polydimethylsiloxane chip with a glass slide through oxygen plasma to obtain a microfluidic chip with a serpentine channel and a Raman detection channel; the microfluidic system is described.
9. The method according to claim 8, characterized in that The serpentine channel is 150 μm wide, and the Raman detection channel is 800 μm wide; the height of the serpentine channel and the Raman detection channel is 100 μm.